Epithelial mesenchymal transition (EMT) and non-small cell lung cancer (NSCLC): a mutual association with airway disease - Mahmood, Malik Quasir; Ward, Chris; Muller, Hans Konrad; Sohal, Sukhwinder Singh; Walters, Eugene Haydn (Medical oncology (Northwood, London, England), 2017)
NSCLC is a leading cause of morbidity and mortality worldwide. It includes adeno- and squamous cell carcinoma. In the background, COPD and smoking play a vital role in development of NSCLC. Local progression and metastasis of NSCLC has been associated with various mechanisms, but in particular by a process called epithelial mesenchymal transition (EMT), which is implicated in COPD pathogenesis. In this study, we have investigated whether expression of EGFR (activation marker) and S100A4, vimentin and N-cadherin (as EMT) is different both in central and leading edge of NSCLC and to what extent related to EMT activity of both small and large airways, stage and differentiation of NSCLC. We have investigated EMT biomarkers (S100A4, vimentin, and N-cadherin), an epithelial activation marker (EGFR) and a vascularity marker (Type-IV collagen) in surgically resected tissue from patients with NSCLC (adeno- and squamous cell carcinoma), and compared them with expression in the corresponding non-tumorous airways. EGFR, S100A4, vimentin, N-cadherin expression was higher in tumor cells located at the peripheral leading edge of NSCLC when compared with centrally located tumor cells of same subjects ( P < 0.01). Type-IV collagen-expressing blood vessels were also more at the leading edge in comparison with central parts of NSCLC. EGFR and S100A4 expression was related to differentiation status ( P < 0.05) and TNM stage ( P < 0.05) of NSCLC. Moreover, EMT markers in the leading edge were significantly related to airway EMT activity, while peripheral edge vascularity of squamous cell carcinoma only was significantly related to large airway Rbm vascularity ( P < 0.05). EGFR- and EMT-related protein expression was markedly high in the peripheral leading edge of NSCLCs and related to tumor characteristics associated with poor prognosis. The relationships between EMT-related tumor biomarker expression and those in the airway epithelium and Rbm provide a background for utility of airway changes in clinical settings.